Mitochondrial-related gene associated to obesity can be modulated by in utero hyperglycemic environment - Silveira, Maruhen A.D. [UNESP] (2019)
We investigated whether mitochondrial-related genes and proteins are modulated by hyperglycemia promoted by gestational diabetes (GDM), thereby increasing neonate obesity predisposition. 19 healthy pregnant women, 16 pregnant women with GDM and their respective neonates were enrolled. Additionally, 19 obese and 19 eutrophic adults were recruited as a reference population. Umbilical cord, peripheral blood and placental (villous and decidua) tissues were collected to evaluate SOD2, PPAR-α and PPARGC-1β and their respective protein expressions. Data from the reference population confirmed that the three genes and proteins were overexpressed in blood cells of obese compared to eutrophic subjects. Only SOD2 was found upregulated in placental villous (fetal side) tissue of GDM women. Therefore, our findings showed an interaction between the hyperglycemic environment and SOD2 modulation, but also indicated that none of the three genes is useful as potential biomarkers for obesity development.